2012
DOI: 10.1007/978-3-642-34549-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Dynamic Structure of an Enterprise by Applying a Fractal Approach to Business Processes

Abstract: Abstract.A promising approach for analyzing and designing an enterprise is to consider it as a complex adaptive system (CAS) able to self-adjust to the changes in the environment. An important part of designing a CAS model is to untangle the dynamic structure of an enterprise. This paper presents a procedure for identifying all processes that exist in an enterprise as well as their interconnections. The procedure makes use of a number of process-assets and asset-processes archetypes. The first ones help to fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Therefore, the current paper could also be considered as a substantial extension and revision of Bider et al [14] based on the experience reported in [22]. In the current paper, the fractal model, first suggested in [14], has been improved by adding more details to the archetypes. Besides the model improvement, this paper includes a review of related literature, and an extended discussion on the usability of FEM.…”
Section: The Background and Structure Of The Papermentioning
confidence: 91%
See 4 more Smart Citations
“…Therefore, the current paper could also be considered as a substantial extension and revision of Bider et al [14] based on the experience reported in [22]. In the current paper, the fractal model, first suggested in [14], has been improved by adding more details to the archetypes. Besides the model improvement, this paper includes a review of related literature, and an extended discussion on the usability of FEM.…”
Section: The Background and Structure Of The Papermentioning
confidence: 91%
“…The current paper has a more theoretical nature than the experience report, the latter being used in the paper to validate and illustrate our line of thought and findings. The experience report [22], in turn, has been built on ideas presented at the conference on Practice of Enterprise Modeling in 2012 (PoEM 2012), see [14]. Therefore, the current paper could also be considered as a substantial extension and revision of Bider et al [14] based on the experience reported in [22].…”
Section: The Background and Structure Of The Papermentioning
confidence: 96%
See 3 more Smart Citations